The Effect of Adding Purple Yam Flour on the Organoleptic Properties of Biscuits - Devita Annisa; Ichsan Affan; Aripin Ahmad; Teuku Muliadi; Eva Fitriyaningsih; Amelia Puteri Nur Azizah; Syuja Rafiqi Arifin (Journal of Nutrition Science, 2023)
Biscuit is a type of dry food that is popular among the community. In the making of biscuits, additional ingredients are added to increase nutritional value, such as the addition of purple yam tuber. Purple yam contains high levels of carbohydrates and calories. Its carbohydrate content has a high amylose level of 26.98-31.02%. One of the food products that can be made into a healthy snack with high fiber and nutritional value is biscuits. The aim of this study is to determine the effect of adding purple yam flour to the acceptability of biscuits as a high fiber snack. This study is experimental using a Completely Randomized Design (CRD) Non-Factorial with 3 treatments and 3 replications. To influence acceptability, sensory tests were conducted on taste, aroma, texture, and color using 25 panelists. The results showed that the acceptability of biscuits with the addition of purple yam flour from the color aspect was most preferred by panelists in treatment A (150 g) compared to B (125 g) and C (100). The addition of purple yam flour has no significant effect on taste, aroma, and texture, while there is a significant effect on color.